Apigenin directly interacts with and inhibits topoisomerase 1 to upregulate CD26/DPP4 on colorectal carcinoma cells - Fux, Julia E.; Lefort, Émilie C.; Rao, Praveen P. N.; Blay, Jonathan (Frontiers in Pharmacology, 2022)
CD26/dipeptidyl peptidase IV (DPP4) is a cell-surface glycoprotein present on most epithelial cells that modulates the local response to external signals. We have previously shown that the dietary flavone apigenin (4′,5,7-trihydroxyflavone) upregulates cell-surface CD26/DPP4 on human colorectal carcinoma (CRC) cells and regulates its activities. We observed a unique synergistic interaction with the CRC chemotherapeutic agent irinotecan, which through its metabolite SN38 elevates CD26 at doses that are sub-cytotoxic. As SN38 interacts with topoisomerase 1 (Topo1) we evaluated whether apigenin influences Topo1 activity. We used a radioimmunoassay to selectively measure CD26 at the cell surface of HT-29 cells following various treatments. Topoisomerase 1 mRNA expression was measured by q-RT-PCR and protein abundance by western blot analysis. Direct inhibition of topoisomerase activity was measured using an assay of DNA supercoil relaxation with recombinant human Topo1. The role of Topo1 in the effect of apigenin was shown both pharmacologically and by siRNA silencing of Topo1. Molecular docking analysis was done with SBD computational software using the CDOCKER algorithm. The interplay between apigenin and irinotecan was not observed when apigenin was combined with other chemotherapeutic drugs including the topoisomerase 2 inhibitors doxorubicin or etoposide. There was no enhancement of irinotecan action if apigenin was replaced with its hydroxylated metabolite luteolin (3′,4′,5,7-tetrahydroxyflavone) or Emodin (6-methyl-1,3,8-trihydroxyanthraquinone), which is an inhibitor of the principal kinase target of apigenin, casein kinase 2 (CK2). Apigenin did not alter Topo1 mRNA expression, but siRNA knockdown of functional Topo1 eliminated the effect of apigenin and itself increased CD26 levels. Apigenin inhibited Topo1 activity in intact HT-29 cells and showed comparable inhibition of purified recombinant human Topo1 enzyme activity to that of SN-38, the active metabolite of irinotecan. Apigenin fits into the complex of Topo1 with DNA to directly inhibit Topo1 enzyme activity. We conclude that apigenin has a unique fit into the Topo1-DNA functional complex that leads to direct inhibition of Topo1 activity, and suggest that this is the basis for the exceptional interaction with the CRC drug irinotecan. A combined action of these two agents may therefore exert a role to limit local signals that facilitate tumour progression.